Definition of indicators to assess the operational safety and environment definition of the elements of air navigation systems - Луппо, О. Є.; Пігур, Я. А. (Proceedings of National Aviation University (archive), 2013)
Considered the methodology of EUROCONTROL in the safety assessment. Developed indicators to assess the operational safety and environment definition of elements of the operation of air navigation systems. Explained the application of the developed indicators. Reflected the structure of documents that need to be developed during the evaluation of operational safety.